The Anisotropy Permeability Evolution and Deformation Behavior of Raw Coal under Cyclic Loading Conditions. (20th January 2023) - Xu, Hanhua
Abstract : As an anisotropic porous media, coal's intrinsic permeability is sensitive to stress variably in different directions. Likewise, the degree of damage sustained by the internal solid skeletal structure under external stresses is anisotropic. Four parameters are introduced: permeability stress-based loss rate ( PEL ) and permeability strain-based loss rate ( PSL ) highlight the stress sensitivity of the intrinsic permeability and deformation characteristics of coal's internal structure during the loading process; stress-based irrecoverable permeability coefficient ( EIP ) and strain-based irrecoverable permeability coefficient ( SIP ) describe the loss of intrinsic permeability and irreversible deformation features in the whole load cycle. Stress sensitivity of the vertical intrinsic permeability is greater than that of the horizontal, and the ability of the vertical internal structure to resist deformation induced by an external load is weaker. During the cyclic loading process for the same coal sample, the stress sensitivity of the latter loading cycle is significantly less than the former.